2008
DOI: 10.3362/1756-3488.2008.026
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional health indicator study of open defecation-free villages in Madhya Pradesh, India

Abstract: India's Total Sanitation Campaign (TSC), started in 1999, has the primary aim of 'eradicating the practice of open defecation by 2012'. This paper describes a cross-sectional health indicator study of four villages-two 'open-defecation free' (ODF) villages and two non-ODF villages) in Madhya Pradesh in 2006. The study included:(a) an epidemiological investigation based on a study population of 1,245 individuals; (b) microbiological and parasitological examinations of 10 per cent of stool samples from study pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
3
5
0
1
Order By: Relevance
“…The overall slippage rate reaches to 27.6% in ODF Sub-districts when observable feces in the compound are added. The nding was similar with the study done in Ethiopia Sidama Zone (25%) [22], and in India (21%) [16]. The study also revealed that 272 (38.2%) households in the study at least one household member practice open defecation which is higher than the national average reported by EDHS and JMP country report [5,6].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall slippage rate reaches to 27.6% in ODF Sub-districts when observable feces in the compound are added. The nding was similar with the study done in Ethiopia Sidama Zone (25%) [22], and in India (21%) [16]. The study also revealed that 272 (38.2%) households in the study at least one household member practice open defecation which is higher than the national average reported by EDHS and JMP country report [5,6].…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, Ethiopia began to adopt a Community-Led Total Sanitation (CLTS) approach which concentrates on empowering local people to analyze the extent and risk of OD and aimed at creating open defecation free (ODF) community [14][15]. Nonetheless, as in other countries such as India and Kenya [16][17], the effect of open defecation free status on diarrheal disease was not yet well explored in Ethiopia. It is hypothesized that ODF status will have signi cant statistical association with diarrheal morbidity.…”
Section: The World Health Organization and United Nations Children's mentioning
confidence: 99%
“…Perbandingannya sakit diare antara penduduk yang tinggal di lingkungan penduduknya masih BABS dengan non BABS di India adalah sebanyak 75 persen penduduk terkena diare dan dysentry sebanyak 15,9 persen pada penduduk desa yang BABS, sementara hanya 23 persen diare dan desentri 2,72 persen terjadi pada penduduk non BABS. (Chakma et al 2008).…”
Section: Pendahuluanunclassified
“…Despite the pervasive belief that child faeces are safe , unsafe disposal of child faeces increases exposure to faecal pathogens in the domestic environment . Infants and young children in LMIC are particularly vulnerable to microbial contamination in their environment through childhood mouthing behaviours during their exploratory stage of development and through contaminated outdoor play spaces .…”
Section: Introductionmentioning
confidence: 99%